2021
DOI: 10.2147/cmar.s316969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hybrid PET/MRI for Gross Tumor Volume (GTV) Delineation in Colorectal Cancer Liver Metastases Radiotherapy

Abstract: Hybrid PET/MRI has been increasingly incorporated into the practice of radiation oncologists since it contains both anatomical and biological data and may bring about personalized radiation plans for each patient. The objective of this study was to evaluate the feasibility of GTV delineation from hybrid PET/MRI compared with that from currentpractice MRI during radiotherapy planning in patients with colorectal liver metastases. Patients and Methods: Twenty-four patients (thirty lesions) with colorectal liver m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Gibson et al recommended that an enlarged GTV margin defined by mpMRI may support focus-enhancing or therapeutic PCa [ 22 ]. Several studies of different tumor sites have also shown that that GTV based on PET/MRI is larger than that obtained from GTV-MRI because of the additional biological information provided by PET, which can reduce the risk of locational errors and affect GTV variation during radiotherapy, thus influencing the radiation dose administered to normal tissue [ 17 , 23 , 24 ]. Therefore, we hypothesized that a larger GTV-PET/MRI may result in the acquisition of a more complete target, allowing adequate irradiation of the lesion, and, thus, affecting the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson et al recommended that an enlarged GTV margin defined by mpMRI may support focus-enhancing or therapeutic PCa [ 22 ]. Several studies of different tumor sites have also shown that that GTV based on PET/MRI is larger than that obtained from GTV-MRI because of the additional biological information provided by PET, which can reduce the risk of locational errors and affect GTV variation during radiotherapy, thus influencing the radiation dose administered to normal tissue [ 17 , 23 , 24 ]. Therefore, we hypothesized that a larger GTV-PET/MRI may result in the acquisition of a more complete target, allowing adequate irradiation of the lesion, and, thus, affecting the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the 68 Ga subgroup, only GTV-MRI was significantly correlated with DSC. As a previous study showed, the spatial overlap between GTV-MRI and GTV-PET/MRI increases as the tumor volume increases [ 23 ]. Draulans C et al investigated the effect of tracer variability on the GTV profile and found that the distribution of SUV% in the prostate was significantly altered in 18 F-PSMA-based images, resulting in increased interobserver variability [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the IMRT, the significance of accurate tumor volumes is re-emphasized. Since [ 18 F]-FDG PET/MRI can concurrently capture both tissue morphology and tumor metabolism information, it can accurately distinguish tumor tissue from neighboring tissues, making it valuable for accurate target identification in radiotherapy [ 55 ].…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…The effect of PET/MRI on GTV has been studied through the observation of the differences among GTV-MRI, GTV-PET, and GTV-PET/MRI [ 55 , 58 , 59 ]. Using GTV-MRI as a reference, Zhang et al evaluated the differences between GTV-PET and GTV-[ 18 F]-FDG PET/MRI in the delineation of colorectal liver metastases and found that GTV-[ 18 F]-FDG PET/MRI had the highest tumor volume [ 55 ].…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…or therapeutic PCa(Gibson E et al 2016). Several studies of different tumor sites have also shown that GTV based on PET/MRI are larger than GTV-MRI because of the additional biological information of PET, which can reduce the risk of locational errors and affect GTV variation during radiotherapy, thus in uencing the radiation dose administered to normal tissue(Ma JT et al 2017;Zhang YN et al 2021;Muijs CT et al 2009…”
mentioning
confidence: 99%